ANALISIS YURIDIS ATAS KLAIM HAK MILIK ATAS TANAH OLEH INSTANSI PEMERINTAH - Sudiro Basana; Muhammad Yamin; Syafruddin Kalo; Faisal Akbar Nasution (jurnal.unprimdn.ac.id, 2023)
We are researching to learn how the government controls land ownership according to the Basic Agrarian Law and what happens when they claim ownership of land. We also want to know how they use the term